2015
DOI: 10.1155/2015/760585
|View full text |Cite
|
Sign up to set email alerts
|

An Herbal Galactagogue Mixture Increases Milk Production and Aquaporin Protein Expression in the Mammary Glands of Lactating Rats

Abstract: Background. Herbal galactagogues have been increasingly used to treat postpartum hypogalactia. The mechanism of action of herbal galactagogues remains unclear. The purpose of this study was to investigate the effect of an herbal galactagogue mixture on milk production and aquaporin (AQP) expression in lactating rats. Methods. Thirty female Sprague Dawley rats were randomized into virgin, lactating + H2O, and lactating + galactagogue groups (n = 10 per group). Lactating rats were administered the decoction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…Otherwise, the stimulation by fenugreek of genes involved in mitochondrial energy metabolism ( Cs , Atp5f1a , Mtco1 ) and particularly those involved in β-oxidation ( Cpt1a , Acads ) suggests that increased ATP synthesis took place in the mammary gland to meet the increased energy requirements associated with increased milk production [ 22 ]. Nevertheless, contrary to Liu et al [ 55 ], we were unable to observe a significant increase in water inflow in response to galactagogue even though mean Aqp1 and Aqp3 expressions were increased at L12 and L21.…”
Section: Discussioncontrasting
confidence: 99%
“…Otherwise, the stimulation by fenugreek of genes involved in mitochondrial energy metabolism ( Cs , Atp5f1a , Mtco1 ) and particularly those involved in β-oxidation ( Cpt1a , Acads ) suggests that increased ATP synthesis took place in the mammary gland to meet the increased energy requirements associated with increased milk production [ 22 ]. Nevertheless, contrary to Liu et al [ 55 ], we were unable to observe a significant increase in water inflow in response to galactagogue even though mean Aqp1 and Aqp3 expressions were increased at L12 and L21.…”
Section: Discussioncontrasting
confidence: 99%
“…The molecular mechanisms underlying the action of herbal galactagogues remain unknown. Recently, Liu et al (2015) showed in animal models that herbal galactagogues may increase milk secretion by regulating mammary glands' expression and function of aquaporins (AQPs -a family of membrane proteins facilitating water movement across cell membranes). Nevertheless, the existing clinical evidence regarding the efficacy of galactagogues remains insufficient (Zapantis et al 2012).…”
Section: Maternal Knowledge and Use Of Galactagogues In Andean Communmentioning
confidence: 99%
“…Therefore, interventions to increase human milk supply using pharmacological agents might be complicated by safety concerns to women and their infants. Traditionally, herbal remedies have been viewed as good alternatives to prescription medications [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal reports of many herbal remedies supported their potential to enhance human milk supply. These herbal remedies include fenugreek, anise, caraway, fennel, milk thistle, and many others [ 16 , 18 , 21 ]. Fenugreek ( Trigonella arabica Delile) which belongs to the pea family (Leguminosae) is the most widely used herbal galactogogue to enhance human milk supply in many countries [ 22 ].…”
Section: Introductionmentioning
confidence: 99%